APLIKASI MATRIKS QUALITY FUNCTION DEPLOYMENT (QFD) PADA PERANCANGAN ULANG MEJA BELAJAR MINI - Diana Khairani Sofyan; Amri Amri (Universitas Teuku Umar, 2017)
CV. Rapi Kana is a furniture company in Ule Reuleng North Aceh, the company produces cabinets, study chairs, tables, study tables and more. The chair and lecture desk is one of the most closely related factors in improving the quality of student learning. Discomfort in learning to make students less focused and tend to get tired quickly in doing tasks and lecture activities. The main cause lies on the desk used. The lesson used is less suitable for the student body size. Dissociation between study desk and student body size is one of the obstacles in the effort to improve the quality human resources. The impact of desks that arenot in accordance with body size can lead to many students experiencing fatigue. Nonconformity of the desk leads to feelings of discomfort (restlessness), lack of concentration, drowsiness, and so forth. In this case will be done research related to the design of the mini desk, where the study table produced by the company will be analyzed its shortcomings and advantages, followed by redesign for the desk. The design is adapted to the posture of the human body. The method used to start with the determination of product characteristics with Quality Function Deployment (QFD) method and also from the calculation of antropometry data so that the result of mini table design in accordance with consumer desire that is comfortable, effective and efficient.Keywords: Quality Function Deployment (QFD) method, Anthropomentry, Mini tabledesign